Exploring the Impact of Web 2.0 Tools on 21st Century Skills of EFL Learners in Pakistan - Malissa Maria Mahmud; Tehreem Fatima; Tahira Anwar Lashari; Zahra Waheed (MDPI AG, 2023)
In today's globalized world, 21st century skills, such as communication and collaboration, are essential for success. For EFL (English as a foreign language) learners in Pakistan, acquiring these skills can be challenging due to the unique linguistic and cultural barriers they face. Web 2.0 tools, such as Padlet, can provide a platform for EFL learners to improve their communication and collaboration skills in a collaborative and engaging manner. The present study explores the potential of using Padlet to improve the 21st century skills of EFL learners in Pakistan. A quasi-experiment is conducted to compare the effectiveness of using Padlet versus traditional language-learning methods to improve EFL learners' communication and collaboration skills. Learners' perceptions of using Padlet in a collaborative learning context are also investigated. The findings indicated that the use of Padlet has a significant and positive effect on learners' collaboration and communication skills, and that learners have a positive perception of using this tool in a collaborative learning context. The study provides preliminary and context-specific novel insights for language educators and learners on the potential of using Padlet to enhance the 21st century skills of EFL learners in Pakistan.